Il Breviario Grimani e le sue riproduzioni fotografiche nell’Ottocento - Filippin, Sara (MDCCC 1800, 2016)
In the first half of the 1860s two photographic campaigns were conducted on the Grimani Breviary (Venice, Marciana Library): the first one by Antonio Perini, who in 1862 published the photographs of 110 miniatures among the most relevant of the manuscript; the second was realised around 1864 by initiative of the French publisher Léon Curmer, who aimed at publishing thirty-six chromolithographs taken from the same miniatures. Since then the Breviary was no longer photographed. On the basis of archival documents and the analysis of some copies of those reproductions, the paper shows that the negatives obtained by Perini were employed for further editions of the images in 1878, 1880-1881, 1903 and 1906.